Comparing sustainability transition labs across process, effects and impacts: Insights from Canada and Sweden. (July 2022) - Holmén, Johan; Williams, Stephen; Holmberg, John
Abstract: Purposeful transformative change on a level of societal systems, structures and practices is called for in response to contemporary sustainability challenges. Sustainability transition labs and arenas represent a particular set of governance innovations seeking to foster systemic change based on deliberate engagement of multiple actors around complex issues of concern. Most labs aim for long-term contributions in addressing persistent societal challenges and transitioning into sustainability, yet are seldomly evaluated on whether, how and to what extents such contributions become realised in practice. In this paper, we further an analytical framework for comparatively analysing sustainability transition labs and arenas with emphasis on their processes, effects and impacts. The framework is applied on two cases: Energy Futures Lab initiated in Alberta, Canada and the arenas for a Fossil Independent West Sweden - Climate 2030. In particular, the comparison showcases how contextual difference in terms of urgency and turbulence may influence lab activities and how ownership and governance conditions may influence the various directions outputs, effects and wider impacts took. The comparison further illuminates how backcasting and the multi-level perspective may serve as complementary frameworks and tools in lab processes, whose respective role may depend on aspiration and context. We end the paper by providing a series of key considerations in furthering the comparative analytical framework and its application in practice. They orient around the three guiding questions on the why's, what's, and how's of doing comparative research on sustainability transition arenas and labs across their processes, effects and impacts. Highlights: We adapt a framework for cross-case comparison of sustainability transition labs across their processes, effects and impacts The framework is applied on two transition labs in Sweden and Canada engaging with energy and low-carbon transitions Contextual turbulence, urgency and governance conditions permeate the way process, effects and impacts unfold Backcasting and the multi-level perspective provide complementary frameworks in labs, requiring contextually-aware process design Methodological considerations on doing cross case comparisons on sustainability transition labs are discussed